Role of α2δ-3 in regulating calcium channel localization at presynaptic active zones during homeostatic plasticity - Zhang, Yanfeng; Wang, Ting; Cai, Yimei; Cui, Tao; Kuah, Michelle; Vicini, Stefano; Wang, Tingting (Frontiers in Molecular Neuroscience, 2023)
The homeostatic modulation of synaptic transmission is an evolutionarily conserved mechanism that is critical for stabilizing the nervous system. At the Drosophila neuromuscular junction (NMJ), presynaptic homeostatic potentiation (PHP) compensates for impairments in postsynaptic glutamate receptors due to pharmacological blockade or genetic deletion. During PHP, there is an increase in presynaptic neurotransmitter release, counteracting postsynaptic changes and restoring excitation to baseline levels. Previous studies have shown that α2δ-3, an auxiliary subunit of voltage-gated calcium channels (VGCCs), is essential for both the rapid induction and sustained expression of PHP at the Drosophila NMJ. However, the molecular mechanisms by which α2δ-3 regulates neurotransmitter release during PHP remain to be elucidated. In this study, we utilized electrophysiological, confocal imaging, and super-resolution imaging approaches to explore how α2δ-3 regulates synaptic transmission during PHP. Our findings suggest that α2δ-3 governs PHP by controlling the localization of the calcium channel poreforming α1 subunit at presynaptic release sites, or active zones. Moreover, we examined the role of two structural domains within α2δ-3 in regulating neurotransmitter release and calcium channel localization. Our results highlight that these domains in α2δ-3 serve distinct functions in controlling synaptic transmission and presynaptic calcium channel abundance, at baseline in the absence of perturbations and during PHP. In summary, our research offers compelling evidence that α2δ-3 is an indispensable signaling component for controlling calcium channel trafficking and stabilization in homeostatic plasticity.